The Influence Of Human Resource Development, Competence And Leadership On Employee Performance With Workload As An Intervening Variable In The Medan Religious Court - Samsir Toona; Kholilul Kholik; Yohny Anwar (UNIVED Press, 2026)
This study aims to analyze the influence of Human Resource development, competence, and leadership on employee performance with workload as an intervening variable in the Medan Religious Court. This study uses a quantitative approach with data collection techniques through the distribution of questionnaires to all 60 employees, so that the sampling technique used is a saturated sample. The data analysis method used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 3.0 software.The results showed that workload had a positive and significant effect on employee performance with a coefficient of 0.414, t-statistic of 3.854, and p-value of 0.000. Leadership had a positive and significant effect on employee performance with a coefficient of 0.306, t-statistic of 2.325, and p-value of 0.020, but had no significant effect on workload with a coefficient of 0.304, t-statistic of 1.853, and p-value of 0.064. Competency had a positive and significant effect on workload with a coefficient of 0.870, t-statistic of 6.233, and p-value of 0.000, and had a positive and significant effect on employee performance with a coefficient of 0.301, t-statistic of 2.188, and p-value of 0.029. Human resource development has a positive and significant effect on workload with a coefficient of 0.303, t-statistics of 2.502, and p-value of 0.013, and has a positive effect on employee performance with a coefficient of 0.142 and p-value of 0.047.In the indirect influence, the workload was unable to mediate the influence of leadership on employee performance with a coefficient of 0.126, t-statistic of 1.498, and p-value of 0.135. On the other hand, workload was able to mediate the influence of competency on employee performance with a coefficient of 0.360, t-statistic of 3.325, and p-value of 0.001, and was able to mediate the influence of human resource development on employee performance with a coefficient of 0.225, t-statistic of 1.989, and p-value of 0.049. Thus, it can be concluded that competence is the most dominant variable affecting workload, while workload is the most dominant variable affecting employee performance.